Intracellular α-synuclein assemblies are sufficient to alter nanoscale diffusion in the striatal extracellular space - J. Estaun-Panzano; S. Nandi; Q. Gresil; E. Doudnikoff; C. Mazzocco; ML. Arotcarena; MH. Canron; B. Dehay; L. Cognet; E. Bezard (npj Parkinson's Disease)
Abstract α-synucleinopathies progression involves the spread of α-synuclein aggregates through the extracellular space (ECS). Single-particle tracking studies showed that α-synuclein-induced neurodegeneration increases ECS molecular diffusivity. To disentangle the consequences of neuronal loss versus α-synuclein-positive intracellular assemblies formation, we performed near-infrared single-particle tracking to characterise ECS rheology in the striatum of mouse models of α-synucleinopathies. We showed that intracellular α-synuclein assemblies, without neurodegeneration, suffice to alter nanoscale diffusion in the striatal ECS.